El Excentrico, 1967-01-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
January 20, 1967 [5 de enero de 1967]. No volume or issue number. Cover has photo of a newlywed couple, with headline, "The Former Margo Najera Now Mrs. Andy Sepulveda."